P4.112 Sexual Health Meta-Analysis. (13th July 2013) - Becasen, J S; Ford, J; Hogben, M
Abstract : Background: US population-level rates of sexual health indicators such as STI rates have stimulated interest in a public health approach to improving sexual health, focusing in six domains: knowledge, attitudes and norms, communication, healthcare use, sexual behaviour and adverse outcomes We conducted a systematic review of the intervention literature in these domains to assess the extent to which existing research supported sexual health principles: recognition of sexuality as intrinsic to individual health and relationships should have positive outcomes for all partners involved. Methods: Studies were drawn from Medline and PsycInfo databases (English language, adult populations, published between 1996–2011, country with developed public health infrastructure). Sufficient studies for meta-analytic review were in three domains: knowledge, attitudes, and sexual behaviours. To examine main intervention effects within each domain, study's intervention characteristics were extracted to compute the pooled Hedges' g and 95% CIs using the random-effects model. Effect size heterogeneity was measured by I 2 . Results: From 9064 candidates, 21 studies across three domains were included in the meta-analysis. For knowledge, there was a large intervention effect on sexual health knowledge, Hedges' g = 1.32 (0.51–2.14). The pooled effect size for both attitudes and sexual behaviour domains yielded small to medium intervention effects, Hedges' g = 0.58 (0.34–0.81) and 0.25 (0.13–0.37), respectively. Heterogeneity for each domain was substantial (between 91% and 97%). Removal of outliers decreased heterogeneity estimates for all domains (21% to 62%), i.e., small. The final effects sizes for knowledge, attitudes and sexual behaviour were 0.25 (0.03–0.48), 0.21 (0.15–0.28) and 0.10 (0.06–0.15), respectively. Conclusions: Our results indicate that existing intervention efforts focused on sexual health knowledge, attitudes and behaviour have small, but positive significant effects. Studies were not designed to encompass all the domains of sexual health, but when studies were examined by these domains the results were consistent across the studies.